Virtual museum tour in Wasaka Banjarmasin to introduce the collection of leaders and local heroes based on mobile augmented reality technology in the new normal era - Aulia Akhrian Syahidi; Subandi Subandi; Adistya Nadia Azura; Ida Hastuti (Institut Teknologi Dirgantara Adisutjipto, 2021)
Wasaka Museum is one of the museums in Banjarmasin City. However, the information obtained by visitors at this time is only from short writings near the object of the image, and museum guards cannot accompany visitors to get around. Furthermore, the interest of museum visitors has also decreased due to the unavailability of adequate information, minimal services, and the impact of the COVID-19 pandemic. The purpose of this research is to develop applications using Mobile Augmented Reality Technology as a means of promotion, trying to attract visitors with AR interaction treats, and the form of virtual museum tours. The methodology used is the Agile Development Method with the type of Extreme Programming (XP). Then the A/B Testing Method is used to select the user interface design. Marker-Based Tracking is a method of detecting markers so that 3D objects can appear. The conclusion is that the selected interface design is design B with a percentage of 76.9%, all the features in the application have functioned very well, and the results of the usability evaluation with a percentage of 83.33% have an Excellent predicate which means that they can be recommended for further use at the Wasaka Museum Banjarmasin in the New Normal Era.